Decolourisation of dye solution containing azo acid orange 7 by electricity - Mohd Zin, Nur Shaylinda (2005)
Colouring effluent from industrial activities may affect environment and human health. Many methods have been used to decolourise such effluent including using electricity. This study was performed to investigate the behaviour of decolourisation of solution containing Azo Acid Orange 7. This study was focusing on the effect of decolourisation due to current density, dye concentration and duration of current flow. Simple electrochemical cell was prepared by using iron and steel plate electrode. The effectiveness of the method was determined by measuring percentage of colour and absorbance removal. The percentage of colour removal was higher then the percentage of absorbance removal. It is found that decolourisation was directly proportional to current density, duration of electric current flow and concentration of the dye. Based on MINITAB™ analysis current density, duration and concentration does affecting the percentage of colour removal. The efficiency of decolourisation for 100 mg/1 to 200 mg/1 concentration was able to increase up to more 95% of colour removal and more than 88% of absorbance removal when duration was 18 minutes and current density was 120 A/m2.